Radiomics in head and neck squamous cell carcinoma – a leap towards precision oncology - Abhishek Mahajan; Pranjal Rai (Journal for ImmunoTherapy of Cancer)
Immunotherapy has revolutionized head and neck squamous cell carcinoma (HNSCC) treatment, with neoadjuvant chemoimmunotherapy showing promising pathological complete response rates (36–42%). Lin et al introduce a radiomics-clinical nomogram using MRI-derived intratumoral and peritumoral features to predict pCR, addressing a critical clinical gap. Their model, emphasizing the peritumoral region (within 3 mm), achieved high predictive accuracy area under curve (AUC) >0.8. While the multicenter design enhances generalizability, standardizing imaging protocols remains a challenge. Integrating radiomics with the Neck Imaging Reporting and Data System could refine post-treatment assessment. This study advances precision oncology in HNSCC, offering a non-invasive tool for personalized treatment strategies. Future directions include artificial intelligence-driven radiomics and radiogenomics to enhance treatment response prediction and patient selection.